Technology of meat and meat products (Ellis Horwood, 1992)
A contemporary survey of the industrial processes used to prepare meat, which covers freezing, cooking, preservation and comminuted products. Each section is supported by references to the technical literature. Emphasis is placed on qualities which make the product attractive to the consumer.